Analyzing The Impact Of Using Artificial Intelligence (AI) Customer Service On Service - Nasution, Sabrina; Nasution, Muhammad Irwan Padli; Nurbaiti, Nurbaiti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The goal of this study is to analyze the consequences of using customer service artificial intelligence on services to improve service quality at shopee. In today's digital era, many e-commerce companies including shopee are using AI technology. Shopee is the top 5 leading e-commerce in Southeast Asia in 2022.  This study uses quantitative methods with data collection coming from questionnaires. Respondents in this study were 100 people who were users or customers of the shopee application. Simple Linear Regression Analysis, processed by SPSS Version 29, was used for purposive sampling. The Independent Variable in this study is Customer Service Artificial Intelligence and the dependent variable is Service. The results of the study indicate that the impact of using Customer Service AI on Service has succeeded in improving service quality, especially in terms of responsiveness and customer satisfaction.